Interpretasi Inklusifisme Kementerian Agama RI (Telaah Batasan Toleransi dalam Tafsir Tematik Moderasi Beragama) - Amin Harahap, Rakhmat; Shunhaji, Akhmad; Afif, Nur (Journal of Comprehensive Science, 2024)
This thesis concludes that the boundaries of tolerance in the Tafsir Tematik Moderasi Beragama Kementerian Agama RI are generally relative and tentative. The intensity of interpretation conducted by the Kementerian Agama RI is not static or monotonous; rather, it dynamically evolves in line with the changes of the times. This conclusion is based on the findings that the boundaries of tolerance in the Tafsir Tematik Moderasi Beragama by Kementerian Agama RI emphasize the preservation of Islamic aqidâh as a rahmatan lil âlamin. In ibâdah, tolerance includes the freedom to practice rituals according to each individual’s religion, but it does not permit the mixing of rituals from different religions. Lastly, in muâmalah, tolerance involves an attitude of mutual respect and appreciation for moral values while still adhering to the principles of religious morals. This thesis aligns with the views of Anis Malik Thoha (2015), Abd. Moqsith Ghazali (2009), and Ulil Abshar Abdalla (2001) that tolerance is a behavior that creates a more peaceful and harmonious environment, where individuals from various religious backgrounds can live together with mutual respect and support. Despite these similarities, this thesis differs from the perspectives of Firanda Andirja (2021), Muhammad Rifqi Fachrian (2018), and Majelis Ulama Indonesia (2005), which assert that the boundaries of tolerance are determined by the beliefs of each individual. Islam teaches respect for adherents of other religions while maintaining these boundaries to avoid recognizing the truth of other religions. This thesis employs a qualitative method and is a literature review (library research) using the maudhû’i interpretation theory framework. This method is utilized to examine the boundaries of tolerance in the Tafsir Tematik Moderasi Beragama by the Kementerian Agama RI through a thematic interpretation approach with an inclusiveism perspective.